Strategic Ambidexterity and Organizational Performance of Manufacturing Companies in Jakarta, Indonesia - Mariza, Ita; Baskoro, Gembong (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This study identifies factors that improve competitive strategies in manufacturing companies, known as strategic ambidexterity (SA), and their impact on organizational performance to improve production systems as a source of competitive advantage. This survey study was conducted through employee perceptions of SA, by exploiting and exploring firm capacity and capability. Data were collected through a survey directly to the respondents involving 200 employees of manufacturing companies in Jakarta, Indonesia. The method used was a field survey, and the data were analyzed using Structural Equation Modeling (SEM) with Linear Structural Relations (LISREL 9.2). The findings are exploiting organizational capacity has significant effect on SA, exploring organizational capability has a significant effect on SA, and SA has a significant effect on organizational performance. The limitations of this research are it is characterized by cross-sectional and perceptual analysis. The location of all companies involved is only in Jakarta. The managerial implications are that optimal firm performance can be achieved by implementing SA through exploiting organizational capacity to maximize competitiveness in existing markets by optimizing the service quality to customer, improving processes to respond to market feedback, and understanding market needs, and exploring capability to take opportunities in new markets through product innovation, discovering and integrating new technologies, maintaining customers relationships, being flexible and adaptive to the market needs.